CASPAR: a retrospective cohort study of the high-concentration capsaicin topical system in patients with painful diabetic peripheral neuropathy of the feet - Michael Überall; Mariëlle Eerdekens; Tamara Quandel; Sylvia Engelen; Lucia Garcia-Guerra; Tawfik Fajri; Samuel Allen; Rita Freitas; Zoltan Kender (BMJ Open Diabetes Research & Care)
Introduction Painful diabetic peripheral neuropathy (pDPN), a common complication of diabetes, is challenging to treat and negatively impacts quality of life (QoL). Many patients either fail to achieve adequate pain relief with current treatments or suffer from systemic side effects with oral options. This study used data from the German Pain e-Registry (GPeR) to evaluate the high-concentration capsaicin topical system (HCCTS) for treating pDPN of the feet.Research design and methods This retrospective, non-interventional cohort study (CASPAR) included patients with pDPN of the feet who received ≥1 HCCTS treatment (~3-month treatment intervals) and contributed data to the GPeR for ≥12 months. Data were collected on pain intensity, QoL, sleep, mood, concomitant medication, and tolerability.Results Overall, 365 patients with pDPN of the feet were included. Significant reductions in 24-hour average pain intensity (API) were observed from baseline to month 3 (following one HCCTS treatment). Further reductions in mean API score were seen over 12 months with ongoing treatments, whereas API increased in patients who discontinued treatment (baseline to month 12 mean API scores: 61.4 to 8.8 for four HCCTS [∆ −52.6], 59.3 to 16.7 for three HCCTS [∆ −42.6], 56.3 to 31.9 for two HCCTS [∆ −24.4], 57.5 to 51.4 for one HCCTS [∆ −6.1]). Similar trends were seen for sleep, mood, and QoL outcomes. There was a significant reduction in concomitant pain medication use in patients receiving ongoing HCCTS treatments. The most common adverse events were local application-site reactions.Conclusions This real-world study in patients with pDPN of the feet demonstrates that ongoing HCCTS treatments continue to improve pain intensity, mood, and QoL, while concomitant medication use decreases. Benefits from treatment were lost following HCCTS discontinuation. These findings emphasize the importance of ongoing treatments to achieve the potential of HCCTS in improving outcomes for patients with pDPN.